2006
DOI: 10.1007/s10529-006-9238-9
|View full text |Cite
|
Sign up to set email alerts
|

Subunit dissociation and stability alteration of d-hydantoinase deleted at the terminal amino acid residue

Abstract: Two variants of D-hydantoinase (HYD), created by deletion of one amino acid residue of at either the N-or C-terminus, were expressed in Escherichia coli and purified by twostep chromatography. Compared with HYD, HYDc1 with the C-terminal Arg deletion retained 43% activity, while HYDn1 with the N-terminal Ser deletion had no activity using DLHydantoin as substrate. Based on HYD dimer with a molecular weight of 103 kDa, HYDc1 is a monomer of 52 kDa and HYDn1 is a mixture of dimer and monomer. Moreover, HYDc1 dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 21 publications
2
17
0
Order By: Relevance
“…Previous reports have shown that modifications to the C termini of DHP/HYD enzymes could decrease the enzyme activity (9, 48,[53][54][55]. In the D-HYD from B. stearothermophilus and Bacillus thermocatenulatus, the truncated enzymes with a deletion of 40 amino acids on the C terminus have lost 64% of their enzymatic activities (48).…”
Section: Structural Insights Into the Stages Of Lysine Carbamylation-mentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reports have shown that modifications to the C termini of DHP/HYD enzymes could decrease the enzyme activity (9, 48,[53][54][55]. In the D-HYD from B. stearothermophilus and Bacillus thermocatenulatus, the truncated enzymes with a deletion of 40 amino acids on the C terminus have lost 64% of their enzymatic activities (48).…”
Section: Structural Insights Into the Stages Of Lysine Carbamylation-mentioning
confidence: 99%
“…In the D-HYD from B. stearothermophilus and Bacillus thermocatenulatus, the truncated enzymes with a deletion of 40 amino acids on the C terminus have lost 64% of their enzymatic activities (48). In Pseudomonas putida YZ-26, a series of deletions were performed in the D-HYD and all of the truncated enzymes exhibited either low or non-detectable activities (53,54). However, CD spectroscopy showed that these deletions of the C-terminal fragment did not alter the secondary structures of the overall folding (48,54).…”
Section: Structural Insights Into the Stages Of Lysine Carbamylation-mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on different enantioselectivities for various substrates, hydantoinases can be classified into three types: D-, L-or DL-configuration [3,4]. However, the D-hydantoinase from microorganisms has attracted much more attentions because it is used for the production of optically pure D-amino acids that are key intermediates in the synthesis of commercial products such as β-lactam semisynthetic antibiotics, peptides, hormones, pyretroids, and pesticides [5].…”
Section: Introductionmentioning
confidence: 99%
“…Enzymatic assay D-Hydantoinase activity was measured by a colorimetric method (Niu et al 2007). An aliquot of the enzyme was added into the reaction mixture in a total volume of 1.5 ml, contained 100 mM hydantoin and 50 mM TB8.…”
Section: Strain Plasmid Reagents and Equipmentsmentioning
confidence: 99%